Combination therapy with once-weekly glucagon like peptide-1 receptor agonists and dipeptidyl peptidase-4 inhibitors in type 2 diabetes: a case series - Lajthia E; Bucheit JD; Nadpara PA; Dixon DL; Caldas LM; Murchie M; Sisson EM (Centro de Investigaciones y Publicaciones Farmaceuticas, 2019)
Background: National treatment guidelines recommend glucagon-like peptide receptor agonists (GLP-1 RAs) as add-on therapy to oral agents. However, GLP-1 RAs in combination with dipeptidyl peptidase-4 (DPP-4) inhibitors is not recommended due to a lack of evidence. Objective: This case series aims to describe the efficacy and safety of once-weekly GLP-1 RAs administered concomitantly with DPP-4 inhibitors in patients with type 2 diabetes. Methods: A retrospective chart review of electronic medical records at a free health clinic was conducted between July 2014 and September 2016. Patients 18 years and older with type 2 diabetes were included if they received concomitant DPP-4 inhibitor and once-weekly GLP-1 RA therapy with at least one glycated hemoglobin A1c (HbA1c) measurement within three to six months of starting the combination. The primary and secondary outcomes included change in HbA1c and weight, and patient reported adverse events. Results: Out of forty-three patients that received combination DPP-4 inhibitor plus GLP-1 RA therapy, only eighteen received once-weekly GLP-1 RA. At 3 months, the median (IQR) HbA1c and weight change was -0.8% (-4.3 to 2%) and -0.4kg (-4.2 to 5.8 kg) respectively. No patients reached an HbA1c below 7% and only three patients (17%) reached a HbA1c less than 8%. Patient reported adverse effects included gastrointestinal disturbances (28%), hypoglycemic symptoms (17%), and injection site reactions (0.6%). Conclusions: Concomitant use of once-weekly GLP-1 RAs and DPP-4 inhibitors provides only modest improvement in glycemic control with minimal weight loss benefits, which is similar to monotherapy with either agent. The combination is unlikely to provide synergistic effects and is not cost effective. These data support the current recommendations against use of combined incretin therapy.